Combined St. Thomas and Histidine-Tryptophan-Ketoglutarat Solutions for Myocardial Preservation in Heart Transplantation Patients - Lee, K.C.; Chang, C.Y.; Chuang, Y.C.; Sue, S.H.; Yang, H.S.; Weng, C.F.; Lee, Y.T.; Huang, W.S.; Chen, I.C.; Wei, J. (Transplantation proceedings, 2012)
To establish quicker cardiac arrest and less myocardial distension injury during heart procurement, we combined St. Thomas and histidine-tryptophan-ketoglutarate (HTK) solutions for donor heart preservation since June 2008. From June 2008 to March 2010, we enrolled 31 heart transplantation (HT) patients in this study. During heart procurement we initially infused 1,000 mL cold St Thomas cardioplegic solution to achieve cardiac arrest. After procurement, a further 2,000 mL of cold HTK solution was infused at low perfusion pressure. Another 1,000 mL cold HTK solution was perfused before donor heart implantation. We examined donor age, recipient preoperative characteristics, ischemia time, hospital stay, postoperative graft function, major cardiac events, and transplant vasculopathy (TCAD). Twenty-two patients (71.0%) presented with dilated cardiomyopathy and 7 (23.3%) with ischemia cardiomyopathy. There were 23 (76.7%) male donors, and the mean donor age was 38.4 ± 13.8 years. Six patients underwent a redo sternotomy, 1 patient needed a third-do sternotomy, and 1 a seventh sternotomy (third HT) for repeated endocarditis and graft failure. The average ischemia time was 224.9 ± 71.0 minutes and the postoperative hospital stay was 57.7 ± 47.7 days. The surgical mortality (3.2%) was not accompanied by hospital or follow-up mortality. Patient left ventricular ejection fraction postoperative was 59.6 ± 2.3% with good functional status. Major cardiac events occurred in 8 patients (26.7%) without major complications. There were two subjects with TCAD but normal graft function. The correlation between ischemia time and hospital stay was insignificant (r = 0.21; P = .26). Donor heart preservation combining St Thomas cardioplegic arest and low-pressure perfusion with HTK solution seemed to be safe with. short-term survival similar to other approaches.